Sustainable aviation fuels: a review of production technologies, life-cycle emissions, and key challenges - Aaqib Zafar; Muhammad Nauman; Muhammad Usman; Rashid Ali Laghari; Muhammad Imran Akhtar; Azhar Abbas Khosa; Muhammad Kashif Shahzad; Abdur Rahman Shaukat; Sheikh Muhammad Farhan; Muhammad Hamid Abbas; Longfei Chen (Fuel, 2027)

Leakage-aware depth-blocked evaluation of a hybrid CNN–transformer for continuous calcite concentration prediction from single-well conventional logs - Hafiz Hussain Ahmad; Zhishui Liu; Shi Lei; Song Zhaohui; Shaukat Khan; Sohail Ahmed; Muhammad Junaid; Zhixiu Liu (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Turning trash into treasure: bioactive peptides from food waste–a decade of progress in extraction, purification, and applications: a systematic review - Muhammad Bilal; Muhammad Usman; Maratab Ali; Samee-Ullah; Faryal Shaukat; Muhammad Arslan; Zhihua Li; Xiaobo Zou; Yemin Guo; Xia Sun (Critical Reviews in Food Science and Nutrition, 2026)

Life cycle assessment of energy retrofitting: case study of an apartment building - Muhammad Asif; Wahhaj Ahmed; Shahzada Shuja; M.Mobeen Shaukat; Zeyad Amin Al-Absi; Moath Ajlouni (Energy and Buildings, 2026)

Exploring Carissa spinarum as a therapeutic candidate: metabolite profiling and antimicrobial evaluation - Laiba Ali; Shahid Nawaz; Sikandar Ali; Asad Ur Rehman; Iram Liaqat; Shaukat Ali; Muhammad Nauman Aftab (Natural Product Research, 2026)

Heterogeneous catalysts' physicochemical influences on CO2 desorption for amine absorbents regeneration - Abdulrahim Ibrahim; Muhammad Imran–Shaukat; Bin Liu; Min Xiao; Hongxia Gao; Zhiwu Liang; Paitoon Tontiwachwuthikul; Teerawat Sema (Journal of Environmental Chemical Engineering, 2026)

Lithology-driven machine and deep learning modelling for porosity prediction in shale reservoir systems using well logging data - Shaukat Khan; Zhishui Liu; Zhiqiang Lu; Wakeel Hussain; Muhammad Sajid; Manaf Muhammad; Abdul Wahid; Muhammad Ubaid Umar (Earth Science Informatics, 2026)

Anti-inflammatory role of metal and metal oxide nanoparticles: a review of toxicity, green synthesis, and immunomodulatory mechanisms - Rimsha Ashraf; Shaukat Ali; Muhammad Summer; Saima Riaz; Amina Iqbal; Ramzana Bibi; Haiqa Shabbir (Inflammopharmacology, 2026)

Enhanced estimation of total organic carbon in the longmaxi shale formation using supervised machine learning with lithofacies characterization via K-means clustering - Shaukat Khan; Zhishui Liu; Zhiqiang Lu; Wakeel Hussain; Sohail Ahmed; Muhammad Sajid; Hafiz Hussain Ahmad; Obaidullah; Imdadullah (Carbonates and Evaporites, 2026)

Heat and humidity stress aggravate high-fat diet-induced kidney damage in albino rats - Muhammad Mubashar Shaukat; Robina Shaukat; Shaaf Ahmad; Nabila Roohi; Sajjad-Ur-Rahman (Biologia Futura, 2026)

Biochemical and histological alterations in the liver of albino rats fed a carbohydrate-rich diet under chronic heat and humidity stress - Robina Shaukat; Muhammad Mubashar Shaukat; Shaaf Ahmad; Nabila Roohi; Sajjad-Ur-Rahman (Biologia Futura, 2026)

Retraction Note: Therapeutic Potential of Aloe vera and Aloe vera–Conjugated Silver Nanoparticles on Mice Exposed to Hexavalent Chromium - Tooba Nauroze; Shaukat Ali; Shagufta Andleeb; Chaman Ara; Iqra Liaqat; Hina Mushtaq; Samaira Mumtaz; Lubna Kanwal; Afshan Syed Abbas; Shumaila Mumtaz; Muhammad Adeel Farooq; Istaqlal Hussain Khan (Biological Trace Element Research, 2026)

Comparative Evaluation of Antiaging Potential of Cymbopogon Citratus Conjugated Silver Nanoparticles and Citral Against D-galactose Induced Aging in Mice - Rimsha Abaidullah; Shaukat Ali; Ayesha Muzamil; Muhammad Summer; Rabia Mushtaq (Cell Biochemistry and Biophysics, 2026)

A comprehensive review on microplastics: Their presence in surface and ground water, environmental distribution, and impact on human and aquatic systems - Khashia Rashid; Shaukat Ali; Asif Hanif Chaudhry; Nosheen Sial; Muhammad Rizwan Akram; Muhammad Aslam (Science of The Total Environment, 2026)

Adaptive responses of Pseudomonas marginalis to modified atmosphere packaging conditions - Muhammad Asim; Huihui Xu; Yanyin Guo; Aqleem Abbas; Mingkun Jiang; Nana Ji; Faryal Shaukat; Hengjia Ni; Zhengli Wang (International Journal of Food Microbiology, 2026)

Effect of a carbohydrate-rich diet on kidney ultrastructure in albino rats exposed to heat and humidity stress - Robina Shaukat; Muhammad Mubashar Shaukat; Husna Ahmad; Nabila Roohi; Sajjad-ur -Rahman; Rifat Ullah Khan (International Journal of Biometeorology, 2025)

Machine learning-driven porosity prediction: A case study from the Cretaceous Mata Series, Canterbury Basin, New Zealand - Muhammad Ubaid Umar; Shenghe Wu; S.M. Talha Qadri; Wakeel Hussain; Du Wei; Shaukat Khan (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Unveiling divergent crop signals in the face of climate variability and ensemble climate projections using CMIP6 data in the South-West of Pakistan - Beenish Javed; Firdos Khan; Muhammad Abbas; Shaukat Ali (Stochastic Environmental Research and Risk Assessment, 2025)

The statistical panorama of post-combustion carbon capture via non-aqueous absorbents: A comprehensive meta-analysis - Muhammad Imran-Shaukat; Rattanaporn Apaiyakul; Hossein Haghani; Min Xiao; Hongxia Gao; Zhiwu Liang; Paitoon Tontiwachwuthikul; Teerawat Sema (Chemical Engineering Journal, 2025)

Liver response to heat and humidity stress in high fat diet fed rats: a biochemical and histological investigation - Muhammad Mubashar Shaukat; Robina Shaukat; Shaaf Ahmad; Nabila Roohi; Sajjad ur Rahman; Mikhlid H. Almutairi; Abdulwahed Fahad Alrefaei; Rifat Ullah Khan; Sifa Dai (International Journal of Biometeorology, 2025)

Correction: Ipomoea carnea Jacq. ameliorates formalin-induced paw inflammation in rats through modulation of oxidative and inflammatory pathways - Shabab Nasir; Muhammad Usman; Humaira Gul; Malik Saadullah; Maryam Farrukh; Rida Siddique; Bushra Shaukat; Abdullah R. Alanzi; Ana Sanches Silva; Muhammad Ajmal Shah (Inflammopharmacology, 2025)

Development and characterisation of buccal dispersible film, syrup and effervescent granules of extemporaneous antigout remedy - Ayisha Shaukat; Khalid Hussain; Naureen Shehzadi; Muhammad Tanveer Khan; Siddiqa Perveen; Nadeem Irfan Bukhari (Natural Product Research, 2025)

Assessing the anticancer potential of Bergenia ciliata conjugated silk fibroin nanoparticles through histopathological and biomarkers study - Faiza; Shaukat Ali; Muhammad Summer; Faiza Sharif (Journal of Molecular Histology, 2025)

Selecting the best CMIP6 GCMs for application and downscaling studies over Pakistan, Nepal and Bangladesh - Shaukat Ali; Michelle Simões Reboita; Zulfiqar A. Bhutta; Muhammad Arif Goheer; Joao Gabriel Martins Ribeiro; Christie André de Souza; Glauber Willian Ferreira; Jai Das; Rida S. Kiani; Azfar Hussain; Fatima Saeed; Muhammad Adnan Abid; et al. (Acta Geophysica, 2025)

Micro and Nanoplastics in Ecosystems: Interrelated Sources, Risks, Pathways, Consequences, Mitigation, Challenges and Future Recommendations - Tauqeer Hussain; Muhammad Summer; Shaukat Ali; Rana Rashad Mahmood Khan; Muhammad Pervaiz; Zohaib Saeed (Water, Air, & Soil Pollution, 2025)

Molecular Mechanisms Behind Organ-Related Aging and Regulatory Effects of Natural Therapeutics - Rimsha Abaidullah; Shaukat Ali; Muhammad Summer; Hunaiza Tahir (Cell Biochemistry and Biophysics, 2025)

Recent advances in synthesis and modulation of 2D heterostructures for sensing and detection applications - Rumaisa Tariq; Waseem Raza; Karma M. Albalawi; Arshad Hussain; Munir Ahmad; Muhammad Asim Mushtaq; Mohamed H. Helal; Ibrahim A. Shaaban; Shaukat Khan; Muhammad Sufyan Javed (Chemical Engineering Journal, 2025)

Ipomoea carnea Jacq. ameliorates formalin-induced paw inflammation in rats through modulation of oxidative and inflammatory pathways - Shabab Nasir; Muhammad Usman; Humaira Gul; Malik Saadullah; Maryam Farrukh; Rida Siddique; Bushra Shaukat; Abdullah R. Alanzi; Ana Sanches Silva; Muhammad Ajmal Shah (Inflammopharmacology, 2025)

Relative change in accommodation space and sedimentation rates of Jurassic to Middle Eocene sedimentary facies in the NW Himalaya, Pakistan - Tariq Mahmood; Naveed Ahsan; Muhammad Armaghan Faisal Miraj; Shaukat Ali; Faisal Shah; Syed Kamran Ali (Carbonates and Evaporites, 2025)

Multifunctional Magnetic Nanoparticles for Targeted Drug Delivery Against Cancer: A Review of Mechanisms, Applications, Consequences, Limitations, and Tailoring Strategies - Shumaila Riaz; Shaukat Ali; Muhammad Summer; Urva Akhtar; Shehzeen Noor; Rimsha Haqqi; Muhammad Adeel Farooq; Iqra Sardar (Annals of Biomedical Engineering, 2025)

Systematic Computational Designing of Efficient Phenalene and Pyrene Based Derivatives to Tune the Optical and Nonlinear Optical Response - Tazeem Fatima; Shamsa Bibi; Shabbir Muhammad; Shaukat Ali; Muhammad Yaseen (Journal of Fluorescence, 2025)

Role of polyphenolics in the management of rheumatoid arthritis through intracellular signaling pathways: a mechanistic review - Uzma Saleem; Maryam Farrukh; Malik Saadullah; Rida Siddique; Humaira Gul; Aqsa Ahmad; Bushra Shaukat; Muhammad Ajmal Shah (Inflammopharmacology, 2025)

Improved damage assessment of bridges using advanced signal processing techniques of CEEMDAN-EWT and Kernal PCA - Hamza Ahsan Abdullah; Muhammad Usman Hanif; Muhammad Usman Hassan; Janita Mahnoor Shahid; Shaukat Ali Khan; Ather Ali (Engineering Structures, 2025)

Evaluation of antibody titer and associated risk factors of goat pox vaccine against lumpy skin disease in crossbred buffaloes - Adili Abulaiti; Zahid Naseer; Zulfiqar Ahmed; Shijun Tian; Wenju Liu; Muhammad Shoaib; Asghar Khan; Mohamed Abdelrahman; Faisal Ayub Kiani; Abid Hussain; Aftab Shaukat; Umair Riaz; et al. (Veterinary Research Communications, 2025)

Optimization and partial purification of tannase from Bacillus licheniformis AS1 under submerged fermentation and its application - Aqsa Shafique; Hafiz Abdullah Shakir; Muhammad Irfan; Shaukat Ali; Muhammad Khan; Chaman Ara; Noor Khan (Systems Microbiology and Biomanufacturing, 2025)

Therapeutic Role of Probiotics Against Environmental-Induced Hepatotoxicity: Mechanisms, Clinical Perspectives, Limitations, and Future - Shehzeen Noor; Shaukat Ali; Muhammad Summer; Anfah Riaz; Laiba Nazakat; Aqsa (Probiotics and Antimicrobial Proteins, 2025)

Pharmacological modes of plant-derived compounds for targeting inflammation in rheumatoid arthritis: A comprehensive review on immunomodulatory perspective - Laiba Nazakat; Shaukat Ali; Muhammad Summer; Fakiha Nazakat; Shehzeen Noor; Anfah Riaz (Inflammopharmacology, 2025)

Synthesis, Characterization, Phytochemistry, and Therapeutic Potential of Azadirachta indica Conjugated Silver Nanoparticles: A Comprehensive Study on Antidiabetic and Antioxidant Properties - Hunaiza Tahir; Farzana Rashid; Shaukat Ali; Muhammad Summer; Misha Afzal (Biological Trace Element Research, 2025)

Graphene-Based Multi-Nanocomposites: Synthesis, Characterization and Photodegradation Analysis - Adeeba Sadia; Muhammad Irshad; Muhammad Faran Akhtar; Shaukat Ali; Muhammad Summer (Journal of Fluorescence, 2025)

Exposure to spaceflight enhances the virulence of Purpureocillium lilacinum against Tetranychus cinnabarinus: modulation of the host’s enzyme activities and microbiome - Xiaoxiao Wang; Fangzhao Yi; Chengli Zou; Qi Yan; Muhammad Hamid Bashir; Waqar Ahmed; Syed Usman Mahmood; Jianhui Wu; Shaukat Ali (Archives of Microbiology, 2025)

Corrigendum to “An updated comprehensive review of camel milk: Composition, therapeutic properties, and industrial applications” [Food Biosci. 62 (2024) 105531] - Ayman Khaliq; Akhilesh Kumar Mishra; Anuj Niroula; Waqas Nabi Baba; Muhammad Nouman Shaukat; Ahmad Rabbani (Food Bioscience, 2025)

Optimization of Ti3C2T performance through synergistic enhancement of GeO /Ti3C2T heterostructures for ammonium-ion storage - Xinze Zhang; Muhammad Sufyan Javed; Hongjia Ren; Saima Batool; Awais Ahmad; Renqian Tao; Munirah D. Albaqami; Shaukat Khan; Xin Wang; Weihua Han (Chemical Engineering Journal, 2025)

Improving green innovation performance: the role of integrating green customers and suppliers, government regulations, green knowledge integration capability - Sami Ullah; Tooba Ahmad; Muhammad Shafiq; Tariq Mehmood; Mohit Kukreti; Muhammad Rehan Shaukat (Environment, Development and Sustainability, 2024)

Microbial-inoculated biochar for remediation of salt and heavy metal contaminated soils - Hafiz Muhammad Mazhar Abbas; Ummah Rais; Muhammad Mohsin Altaf; Fahd Rasul; Asad Shah; Ashar Tahir; Muhammad Nafees-Ur-Rehman; Muhammad Shaukat; Haider Sultan; Ruilong Zou; Mohammad Nauman Khan; Lixiao Nie (Science of The Total Environment, 2024)

An updated comprehensive review of camel milk: Composition, therapeutic properties, and industrial applications - Ayman Khaliq; Akhilesh Kumar Mishra; Anuj Niroula; Waqas Nabi Baba; Muhammad Nouman Shaukat; Ahmad Rabbani (Food Bioscience, 2024)

Zebrafish as an innovative model for exploring cardiovascular disease induction mechanisms and novel therapeutic interventions: a molecular insight - Shaukat Ali; Maryam Zulfiqar; Muhammad Summer; Mahnoor Arshad; Shehzeen Noor; Laiba Nazakat; Abdullah Javed (Molecular Biology Reports, 2024)

Pharmacological and immunomodulatory modes of action of medically important phytochemicals against arthritis: A molecular insight - Aqsa; Shaukat Ali; Muhammad Summer; Saima Yousaf; Laiba Nazakat; Shehzeen Noor (Molecular Biology Reports, 2024)

RETRACTED ARTICLE: Therapeutic Potential of Aloe vera and Aloe vera–Conjugated Silver Nanoparticles on Mice Exposed to Hexavalent Chromium - Tooba Nauroze; Shaukat Ali; Shagufta Andleeb; Chaman Ara; Iqra Liaqat; Hina Mushtaq; Samaira Mumtaz; Lubna Kanwal; Afshan Syed Abbas; Shumaila Mumtaz; Muhammad Adeel Farooq; Istaqlal Hussain Khan (Biological Trace Element Research, 2024)

Quantitative assessment of Nigella sativa and conjugated silver nanoparticles against hexavalent chromium toxic effects on sperm function - Tooba Nauroze; Shaukat Ali; Shagufta Andleeb; Chaman Ara; Lubna Kanwal; Samaira Mumtaz; Muhammad Summer; Rizwan Ullah (Toxicon, 2024)

MoS2@Ti3C2T Heterostructure: A new negative electrode material for Li-Ion hybrid supercapacitors - Salamat Ali; Muhammad Sufyan Javed; Khalid Umer; Jiatai Wang; Yujun Fu; Shunlian Kong; Shaukat Khan; Awais Ahmad; Anand Parkash; Munirah D. Albaqami; Annu; Jing Qi; et al. (Chemical Engineering Journal, 2024)

Revealing the molecular mechanisms in wound healing and the effects of different physiological factors including diabetes, age, and stress - Muhammad Summer; Shaukat Ali; Umaima Fiaz; Tauqeer Hussain; Rana Rashad Mahmood Khan; Hashim Fiaz (Journal of Molecular Histology, 2024)

Exploring the underlying pharmacological, immunomodulatory, and anti-inflammatory mechanisms of phytochemicals against wounds: a molecular insight - Anfah Riaz; Shaukat Ali; Muhammad Summer; Shehzeen Noor; Laiba Nazakat; Aqsa; Muhammad Sharjeel (Inflammopharmacology, 2024)

Recent advancements of nanotechnology in fish aquaculture: an updated mechanistic insight from disease management, growth to toxicity - Muhammad Sharjeel; Shaukat Ali; Muhammad Summer; Shehzeen Noor; Laiba Nazakat (Aquaculture International, 2024)

Inflammatory response of nanoparticles: Mechanisms, consequences, and strategies for mitigation - Muhammad Summer; Rimsha Ashraf; Shaukat Ali; Horacio Bach; Shehzeen Noor; Qudsia Noor; Saima Riaz; Rana Rashad Mahmood Khan (Chemosphere, 2024)

Comparative transcriptome analysis reveals disruption of Plutella xylostella immune system by fungal peptide cyclosporin C - Shaukat Ali; Xiaochen Zhang; Tianxiang Gao; Muhammad Hamid Bashir; Xingmin Wang (Journal of Invertebrate Pathology, 2024)

Spectrophotometrically, Spectroscopically, Microscopically and Thermogravimetrically Optimized TiO2 and ZnO Nanoparticles and their Bactericidal, Antioxidant and Cytotoxic Potential: A Novel Comparative Approach - Hunaiza Tahir; Farzana Rashid; Shaukat Ali; Muhammad Summer; Rimsha Abaidullah (Journal of Fluorescence, 2024)

Assessment of the impacts of climate change on the construction of homogeneous climatic regions and ensemble climate projections using CMIP6 data over Pakistan - Muhammad Abbas; Firdos Khan; Yuei-An Liou; Hamd Ullah; Beenish Javed; Shaukat Ali (Atmospheric Research, 2024)

Miniaturizing Power: Harnessing Micro-Supercapacitors for advanced micro-electronics - Qazi Muhammad Saqib; Abdul Mannan; Muhammad Noman; Mahesh Y. Chougale; Chandrashekhar S. Patil; Youngbin Ko; Jungmin Kim; Swapnil R. Patil; Muhammad Yousuf; Rayyan Ali Shaukat; Young Pyo Jeon; Deepak Dubal; et al. (Chemical Engineering Journal, 2024)

Enhanced climate projections over Sindh, Pakistan: a bayesian model averaging ensemble methodology - Aatka Irfan; Firdos Khan; Muhammad Abbas; Shaukat Ali (Modeling Earth Systems and Environment, 2024)

Mechanisms of medicinal, pharmaceutical, and immunomodulatory action of probiotics bacteria and their secondary metabolites against disease management: an overview - Sundas Nasreen; Shaukat Ali; Saiqa Andleeb; Muhammad Summer; Tauqeer Hussain; Kaleem Imdad; Chaman Ara; Hafiz Muhammad Tahir (Folia Microbiologica, 2024)

Evaluating the Effect of pH, Temperature and Concentration on Antioxidant and Antibacterial Potential of Spectroscopically, Spectrophotometrically and Microscopically Characterized Mentha Spicata Capped Silver Nanoparticles - Tahreem Tanveer; Shaukat Ali; Nazish Mazhar Ali; Muhammad Adeel Farooq; Muhammad Summer; Ali Hassan; Fareha Ali; Muhammad Irfan; Lubna Kanwal; Hafsa Shahzad; Rahila Islam (Journal of Fluorescence, 2024)

Evaluation of irrigation, drinking, and risk indices for water quality parameters of alpine lakes - Rizwan Ullah; Said Muhammad; Wajid Ali; Sehrish Amin; Sardar Khan; Atta Rasool; Abd El-Latif Hesham; Muhammad Umar; Shaukat Ali; Shahid Iqbal; Ashfaq Ahmad (Environmental Geochemistry and Health, 2024)

Exploring the underlying correlation between microbiota, immune system, hormones, and inflammation with breast cancer and the role of probiotics, prebiotics and postbiotics - Muhammad Summer; Ayesha Sajjad; Shaukat Ali; Tauqeer Hussain (Archives of Microbiology, 2024)

Spectrophotometric, microscopic, crystallographic and X-ray based optimization and biological applications of Olea paniculata leaf extract mediated silver nanoparticles - Muhammad Faran Akhtar; Muhammad Irshad; Shaukat Ali; Muhammad Summer; Muhammad Jawad; Muhammad Faizan Akhter; Muhammad Adeel Farooq; Ghulam Asghar (South African Journal of Botany, 2024)

UV-spectrophotometric Optimization of Temperature, pH, Concentration and Time for Eucalyptus Globulus Capped Silver Nanoparticles Synthesis, their Characterization and Evaluation of Biological Applications - Ansar Aziz Subhani; Muhammad Irshad; Shaukat Ali; Muhammad Jawad; Muhammad Faran Akhtar; Muhammad Summer (Journal of Fluorescence, 2024)

Evaluating the Morpho-physiological Responses of Stevia (Stevia rebaudiana) to Foliar Application of Various Plant Growth Promoters Under Drought Stress - Fatima Ahmadzai; Kanval Shaukat; Hafiz Mohammad Akram; Mahmood ur Rehman Ansari; Noreen Zahra; Abdul Samad; Mereen Nizar; Muhammad Bilal Hafeez; Ali Raza (Journal of Crop Health, 2024)

A decline in snow cover area of Passu and Ghulkin valleys between 1995 and 2022 - Imran Hussain; Mumtaz Ali; Sher Muhammad; Wajid Hassan; Salar Ali; Zakir Hussain; Syed Hammad Ali; Shaukat Ali; Muhammad Younis Khan (Journal of Mountain Science, 2023)

Exploring the electrochemical properties of CuSe-decorated NiSe2 nanocubes for battery-supercapacitor hybrid devices - Mudassir Hayat; Yuxue Zhou; Muhammad Zia Ullah Shah; Muhammad Sana ullah; Muhammad Bilal Hanif; Hongying Hou; Umar Arif; Shaukat Khan; Ahmed M. Hassan; Ammar M. Tighezza; Muhammad Sajjad; Raghavender Vadla (Chemosphere, 2023)

Permo-Triassic cyclicity on the western shoulder of Muzaffarabad-Hazara paleo-high, during the oceanisation of Neo-Tethys - Tariq Mahmood; Naveed Ahsan; Muhammad Armaghan Faisal Miraj; Shaukat Ali; Saif ur Rahman; Muhammad Jawad Munawar (Marine and Petroleum Geology, 2023)

An efficient virus-induced gene silencing of PDS gene in Solanum lycopersicum (cv. Rio Grande) and its functional analysis - Iqra Mehboob; Muhammad Mughees; Ayesha Baig; Shaukat Ali; Yasar Sajjad; Shahid Iqbal; Zahoor Hussain; Sajid Fiaz; Farhat Abbas; Kotb A. Attia; Asmaa M. Abushady; Mohammad Maroof Shah (Brazilian Journal of Botany, 2023)

Aspartame, a Synthetic Dipeptide Mediated Biochemical and Histopathological Alterations in Hepato-nephric Tissues of Mice and Pharmaceutical Intervention by Sesame Oil - Chaman Ara; Memoona Arshad; Shaukat Ali; Hafiz Abdullah Shakir; Muhammad Summer; Muhammad Khan; Iram Liaqat; Madeeha Arshad (International Journal of Peptide Research and Therapeutics, 2023)

Biochar amendment for reducing the environmental impacts of reclaimed polluted sediments - Dario Liberati; Syed Wasif Ahmed; Nafeesa Samad; Roberta Mugnaioni; Sundas Shaukat; Muhammad Muddasir; Sara Marinari; Paolo De Angelis (Journal of Environmental Management, 2023)

Seismic Interactions Between Northern Terminus of Ornahc-Nal and Hoshab Faults Based on Source Mechanism Investigation of 06 May 2022 Mw 5.4 Khuzdar Earthquake - Ahmed Zeeshan Shaukat; Mohammad Tahir; Tahir Iqbal; Talat Iqbal; Muhammad Ali Shah (Pure and Applied Geophysics, 2023)

Synergistic neuroprotection by phytocompounds of Bacopa monnieri in scopolamine-induced Alzheimer’s disease mice model - Shehla Shoukat; Muhammad Amir Zia; Muhammad Uzair; Roua A. Alsubki; Kaynat Sajid; Sana Shoukat; KOTB A. Attia; Sajid Fiaz; Shaukat Ali; Itoh Kimiko; Ghulam Muhammad Ali (Molecular Biology Reports, 2023)

Boosting the energy storage performance of aqueous NH4+ symmetric supercapacitor based on the nanostructured molybdenum disulfide nanosheets - Muhammad Sufyan Javed; Xiaofeng Zhang; Salamat Ali; Syed Shoaib Ahmad Shah; Awais Ahmad; Iftikhar Hussain; Shahid Hussain; Shaukat Khan; Mohamed Ouladsmane; Sayed M. Tag ElDin; Waqas Ul Arifeen; Weihua Han (Chemical Engineering Journal, 2023)

Therapeutic and immunomodulatory role of probiotics in breast cancer: A mechanistic review - Muhammad Summer; Shaukat Ali; Umaima Fiaz; Hafiz Muhammad Tahir; Muhammad Ijaz; Shumaila Mumtaz; Rabia Mushtaq; Rida Khan; Hafsa Shahzad; Hashim Fiaz (Archives of Microbiology, 2023)

Influence of the chronic groundwater fluoride consumption on cholinergic enzymes, ACHE and BCHE gene SNPs and pro-inflammatory cytokines: A study with Pakistani population groups - Sara Bibi; Rabia Habib; Sania Shafiq; Syed Sayyam Abbas; Shaiza Khan; Syed Ali Musstjab Akber Shah Eqani; Eugenie Nepovimova; Mansoor Shaukat Khan; Kamil Kuca; Syed Muhammad Nurulain (Science of The Total Environment, 2023)

Modelling the impact of climate change on dengue outbreaks and future spatiotemporal shift in Pakistan - Alia Saeed; Shaukat Ali; Firdos Khan; Sher Muhammad; Michelle Simões Reboita; Abdul Wali Khan; Muhammad Arif Goheer; Mumtaz Ali Khan; Ramesh Kumar; Aamer Ikram; Aliya Jabeen; Sathirakorn Pongpanich (Environmental Geochemistry and Health, 2023)

Hydrothermal assisted synthesis of hierarchical SnO2 micro flowers with CdO nanoparticles based membrane for energy storage applications - Ehsan Ullah; Muhammad Zia Ullah Shah; Syed Awais Ahmad; Muhammad Sajjad; Shaukat Khan; Fatimah M. Alzahrani; Adel E.M. Yahya; Sayed M. Eldin; Bhargav Akkinepally; A. Shah; Shenghui Guo (Chemosphere, 2023)

Glycerol ginger extract addition to edible coating formulation for preventing oxidation and fungal spoilage of stored walnuts - Muhammad Nouman Shaukat; Rosa Palmeri; Cristina Restuccia; Lucia Parafati; Biagio Fallico (Food Bioscience, 2023)

Assessment of knowledge, perception, practices and drivers of antimicrobial resistance and antimicrobial usage among veterinarians in Pakistan - Ayesha Saman; Mamoona Chaudhry; Muhammad Ijaz; Waseem Shaukat; Muhammad Usman Zaheer; Ana Mateus; Abdul Rehman (Preventive Veterinary Medicine, 2023)

Production performance, protein digestibility, gut health and economic efficiency in sexed broilers with super dozing of lysine - Najam us Sahar; Muhammad Shoaib; Muhammad Aslam Mirza; Shaukat Ali Bhatti; Shahzad Ashraf; Noreen Aslam; Alishbah Roobi; Muhammad Arslan Asif (Tropical Animal Health and Production, 2023)

Chemopreventive role of probiotics against cancer: a comprehensive mechanistic review - Shehzeen Noor; Shaukat Ali; Shumaila Riaz; Iqra Sardar; Muhammad Adeel Farooq; Ayesha Sajjad (Molecular Biology Reports, 2023)

Wavelet coherence of monsoon and large‐scale climate variabilities with precipitation in Pakistan - Azfar Hussain; Jianhua Cao; Shaukat Ali; Waheed Ullah; Sher Muhammad; Ishtiaq Hussain; Haider Abbas; Kalpana Hamal; Shankar Sharma; Mobeen Akhtar; Xiuqin Wu; Jinxing Zhou (International Journal of Climatology, 2022)
Monsoon and its teleconnection with earth system internal processes affect the spatiotemporal distribution of precipitation and water resources . In this paper, the wavelet coherence analysis has been utilized, a time and frequency domain methodology for comparing the spectral features of two independent time series superior to linear approaches. This technique is used to capture the significant modes of variabilities in the Indian Summer Monsoon Index (ISMI) and large‐scale climate indices (CIs) between ocean–atmosphere oscillations, like Indian Ocean Dipole (IOD), El Niño–Southern Oscillation (ENSO), Pacific Decadal Oscillation (PDO), Southern Oscillation Index (SOI), North Atlantic Oscillation (NAO), Atlantic Multidecadal Oscillation (AMO), and Arctic Oscillation (AO) over Pakistan. Precipitation time series during 1960–2016 revealed significant interannual coherences with ISMI, whereas the remaining CIs (IOD, ENSO, PDO, SOI, NAO, AMO, and AO) revealed interannual, decadal and interdecadal coherences. However, AO revealed strongest coherences in R‐II, III, and VI at interdecadal scales among all CIs. Overall, the interannual cycles on ISMI are 2.8 years, IOD 1–5.3 years, PDO 0–5.3 years, SOI 1–5.3 years, NAO 0–5 years, AO 0–5 years, and AMO 0–8.3 years. Whereas, the remaining CIs shared interdecadal coherences over particular regions. The ISMI displayed coherences (except in the UIB) with the large‐scale CIs over various homogenous regions on an interannual scale. The dominant influence of ISMI is observed in R‐II and III; the significant coherences in R‐II ranged from ~8 to 32 months (~0.8–2.8 years). The IOD and NAO have major coherences than the remaining large‐scale CIs ranging from ~16 to 64 months (1.3–5.3 years). The AO has the most significant coherences observed in R‐II, III, and VI on the decadal/interdecadal scale from 128 months and above (almost 10–15 years). On a 1.0‐year timescale, all homogenous regions demonstrated strong intermittent coherence with ISMI, IOD, ENSO, PDO, SOI, NAO, AMO, and AO. These findings have substantial implications for decision‐makers and scientists in Pakistan looking to enhance water resource planning and operations in the face of future climate uncertainties.

Observed trends and variability of seasonal and annual precipitation in Pakistan during 1960–2016 - Azfar Hussain; Jianhua Cao; Shaukat Ali; Sher Muhammad; Waheed Ullah; Ishtiaq Hussain; Mobeen Akhtar; Xiuqin Wu; Yinghui Guan; Jinxing Zhou (International Journal of Climatology, 2022)
Long‐term precipitation monitoring plays a vital role in water resource management and disaster prevention and mitigation. This study assesses spatial and temporal trends in seasonal and annual precipitation in Pakistan between 1960 and 2016 at an interannual scale. The Mann–Kendall (MK) test, Sen's slope (SS) estimator, and Sequential Mann–Kendall (SQMK) test were employed to assess trends. Cluster analysis and L ‐moment approach were used to identify the homogenous precipitation regions. In general, increasing precipitation trends between 1960 and 2016 were evident. Results indicated increasing precipitation in winter, autumn, summer and annual scale at the rates of 0.20, 2.18, 5.16, and 10.89 mm·decade −1 , respectively. In spring, the precipitation trend shows a decreasing trend at −0.67 mm·decade −1 . Moreover, a significant decreasing trend occurred in winter in southern Pakistan. The overall increasing trends were more noticeable between 1960 and 1988, compared to the declining precipitation during 1989–2016. SQMK analysis indicates a clear downward trend in most regions during 1989–2016, except in autumn. Annual precipitation has increased topographically except at 500 m and 1,500 m during 1960–2016 with a significant increase of 1.37 mm·decade −1 at elevation

Efficacy of cow and buffalo dung on vermiremediation and phytoremediation of heavy metals via Fourier-transform infrared spectroscopy and comet assay - Anum Naseer; Saiqa Andleeb; Abdul Basit; Shaukat Ali; Muhammad Siraj ud-Din; Nazish Mazhar Ali; Iram Liaqat; Aisha Nazir (Environmental Science and Pollution Research, 2022)

In Silico Dissection and Expression Analysis of Sucrose Synthase Gene Family in Sugarcane - Muhammad Noman; Iqra Siddique; Bilal Saleem; Saiqa Ilyas; Shaukat Ali; Muhammad Ramzan Khan (Sugar Tech, 2022)

Plant Growth Promoters Alleviate Oxidative Damages and Improve the Growth of Milk Thistle (Silybum marianum L.) Under Salinity Stress - Noreen Zahra; Abdul Wahid; Muhammad Bilal Hafeez; Kanval Shaukat; Sobia Shahzad; Tariq Shah; Mohammed Nasser Alyemeni (Journal of Plant Growth Regulation, 2022)

Early summer surface air temperature variability over Pakistan and the role of El Niño–Southern Oscillation teleconnections - Irfan Ur Rashid; Muhammad Adnan Abid; Mansour Almazroui; Fred Kucharski; Muhammad Hanif; Shaukat Ali; Muhammad Ismail (International Journal of Climatology, 2022)
Early summer (May–June) is the season where the surface air temperature (SAT) variability is largest and may result in extreme temperature conditions over Pakistan. Therefore, we analysed the early summer interannual SAT variability over Pakistan for the period 1981–2018 using observational dataset and model simulations. We noted that upper‐level anticyclonic circulation anomalies over Pakistan, which are associated with upper to the middle tropospheric descending motion, favour clear skies with an increase in net shortwave radiation that leads to extreme surface warming over the region. Moreover, the El Niño–Southern Oscillation (ENSO) based on Niño3.4 SST index is negatively associated with SAT anomalies over Pakistan. The cold ENSO phase favours the positive geopotential height anomalies due to the strengthening of the Walker circulation that enhance the sinking motion and result in less cloudiness leading to the extreme higher surface temperature conditions over Pakistan, while the opposite happens in the warm ENSO phase. Moreover, the Saudi‐KAU Atmospheric Global Climate Model (AGCM) simulated large‐scale patterns that are in good agreement with the observations. Sensitivity experiments with the AGCM confirm that cold SST anomalies in the ENSO region significantly favour above‐normal SAT anomalies over Pakistan, while the opposite happens in the warm ENSO phase. These results are important to understand and potentially predict regional heatwaves over the South Asian region, particularly over Pakistan.

Geochemical characteristics of coal seams within the Paleocene Patala Formation, Central Salt Range coal mines (Punjab), Northern Pakistan - Muhammad Sajid; Natasha Khan; Faisal Shah; Muhammad Kashif; Shaukat Khan (Journal of Sedimentary Environments, 2022)

Correction to: Molecular detection of Cryptosporidium: an emerging parasite in different water sources of 2010 flood‑affected district Nowshera, Pakistan - Shaukat Ali Khan; Imran Khan; Izaz Ali; Amir Muhammad Khan; Muhammad Anees; Khurshaid Ali Khan; Wajid Rashid; Noorul Akbar (Archives of Microbiology, 2022)

Aging and its treatment with vitamin C: a comprehensive mechanistic review - Shumaila Mumtaz; Shaukat Ali; Hafiz Muhammad Tahir; Syed Akif Raza Kazmi; Hafiz Abdullah Shakir; Tafail Akbar Mughal; Samaira Mumtaz; Muhammad Summer; Muhammad Adeel Farooq (Molecular Biology Reports, 2021)

Foliar Spray of Natural and Synthetic Plant Growth Promoters Accelerates Growth and Yield of Cotton by Modulating Photosynthetic Pigments - Muhammad Shaukat; Ashfaq Ahmad; Tasneem Khaliq; Irfan Afzal; Sher Muhammad; Bushra Safdar; Sabir Hussain Shah (International Journal of Plant Production, 2021)

Lethal and sublethal effects of emamectin benzoate on life-table and physiological parameters of citrus red mite, Panonychus citri - Muhammad Musa Khan; Muhammad Waqar Ali; Muhammad Hafeez; Ze-Yun Fan; Shaukat Ali; Bao-Li Qiu (Experimental and Applied Acarology, 2021)

Evaluation of sex steroid hormones and reproductive irregularities in diethyl phthalate-exposed premature mice: modulatory effect of raw honey against potential anomalies - Chaman Ara; Asmatullah; Faiza Yaseen; Shaukat Ali; Hafiz Abdullah Shakir; Muhammad Khan; Shagufta Andleeb; Nageena Ramzan (Environmental Science and Pollution Research, 2021)

Evaluation of Cadmium Chloride-Induced Toxicity in Chicks Via Hematological, Biochemical Parameters, and Cadmium Level in Tissues - Shaukat Ali; Saleha Bashir; Shumaila Mumtaz; Hafiz Abdullah Shakir; Chaman Ara; Farooq Ahmad; Hafiz Muhammad Tahir; Mehwish Faheem; Muhammad Irfan; Azeem Masih; Mazhar Ulhaq; Saiqa Andleeb (Biological Trace Element Research, 2021)

Molecular detection of Cryptosporidium: an emerging parasite in different water sources of 2010 flood-affected district Nowshera, Pakistan - Shaukat Ali Khan; Imran Khan; Izaz Ali; Amir Muhammad Khan; Muhammad Anees; Khurshaid Ali Khan; Wajid Rashid; Noorul Akbar (Archives of Microbiology, 2021)

Effect of milk or milk replacer offered at varying levels on growth performance of Friesian veal calves - Muhammad Khalid Qadeer; Shaukat Ali Bhatti; Haq Nawaz; Muhammad Sajjad Khan (Tropical Animal Health and Production, 2021)

The effects of some heavy metals on some fish species - Saba Naeem; Muhammad Ashraf; Masroor Ellahi Babar; Sana Zahoor; Shaukat Ali (Environmental Science and Pollution Research, 2021)

Biosynthesis and industrial applications of α-amylase: a review - Muhammad Adeel Farooq; Shaukat Ali; Ali Hassan; Hafiz Muhammad Tahir; Samaira Mumtaz; Shumaila Mumtaz (Archives of Microbiology, 2021)

Ensemble learning based automatic detection of tuberculosis in chest X-ray images using hybrid feature descriptors - Muhammad Ayaz; Furqan Shaukat; Gulistan Raja (Physical and Engineering Sciences in Medicine, 2021)

Experimental investigations of arsenic adsorption from contaminated water using chemically activated hematite (Fe2O3) iron ore - Abdul Qayoom Memon; Shoaib Ahmed; Zulfiqar Ali Bhatti; Ghulamullah Maitlo; Abdul Karim Shah; Shaukat Ali Mazari; Atta Muhammad; Abdul Sattar Jatoi; Ghulam Abbas Kandhro (Environmental Science and Pollution Research, 2021)

A review of gas chromatographic techniques for identification of aqueous amine degradation products in carbonated environments - Idris Mohamed Saeed; Shaukat Ali Mazari; Peter Alaba; Brahim Si Ali; Badrul Mohamed Jan; Wan Jeffrey Basirun; Yahaya Muhammad Sani; Sabzoi Nizzamuddin; Nabisab Mujawar Mubarak (Environmental Science and Pollution Research, 2021)

Variability and Predictability of Summer Monsoon Rainfall over Pakistan - Muhammad Adnan; Firdos Khan; Nadia Rehman; Shaukat Ali; Sher Shah Hassan; Muhammad Mubashar Dogar; Shahbaz Mehmood; Shabehul Hasson (Asia-Pacific Journal of Atmospheric Sciences, 2021)

Future climatic changes, extreme events, related uncertainties, and policy recommendations in the Hindu Kush sub-regions of Pakistan - Shaukat Ali; Alia Saeed; Rida Sehar Kiani; Sher Muhammad; Firdos Khan; Romaisa Babar; Asif Khan; Muhammad Shahid Iqbal; Muhammad Arif Goheer; Wajid Naseem; Shah Fahad (Theoretical and Applied Climatology, 2021)

SARS-CoV-2 nucleocapsid and Nsp3 binding: an in silico study - Muhammad Tahir Khan; Muhammad Tariq Zeb; Hina Ahsan; Abrar Ahmed; Arif Ali; Khalid Akhtar; Shaukat Iqbal Malik; Zhilei Cui; Sajid Ali; Anwar Sheed Khan; Manzoor Ahmad; Dong-Qing Wei; et al. (Archives of Microbiology, 2021)

Molybdenum Application Regulates Oxidative Stress Tolerance in Winter Wheat Under Different Nitrogen Sources - Muhammad Imran; Xuecheng Sun; Saddam Hussain; Usman Ali; Muhammad Shoaib Rana; Fahd Rasul; Shadab Shaukat; Chengxiao Hu (Journal of Soil Science and Plant Nutrition, 2020)

Efficient synthesis of 2,3-diarylbenzo[b]thiophene molecules through palladium (0) Suzuki–Miyaura cross-coupling reaction and their antithrombolyitc, biofilm inhibition, hemolytic potential and molecular docking studies - Nosheen Sial; Nasir Rasool; Komal Rizwan; Ataf Ali Altaf; Shaukat Ali; Ayesha Malik; Muhammad Zubair; Arusa Akhtar; Samia Kausar; Syed Adnan Ali Shah (Medicinal Chemistry Research, 2020)

Cardiac toxicity of heavy metals (cadmium and mercury) and pharmacological intervention by vitamin C in rabbits - Shaukat Ali; Zubia Awan; Shumaila Mumtaz; Hafiz Abdullah Shakir; Farooq Ahmad; Mazhar Ulhaq; Hafiz Muhammad Tahir; Muhammad Siddique Awan; Saima Sharif; Muhammad Irfan; Muhammad Adeeb Khan (Environmental Science and Pollution Research, 2020)

Characterization and synthetic biology of lipase from Bacillus amyloliquefaciens strain - Muhammad Tahir Khan; Aman Chandra Kaushik; Qurrat ul ain Rana; Shaukat Iqbal Malik; Anwar Sheed Khan; Dong-Qing Wei; Wasim Sajjad; Shabir Ahmad; Sajid Ali; Ameenullah; Muhammad Irfan (Archives of Microbiology, 2020)

Dose and duration-dependent toxicological evaluation of lead acetate in chicks - Saeeda Hussain; Shaukat Ali; Shumaila Mumtaz; Hafiz Abdullah Shakir; Farooq Ahmad; Hafiz Muhammad Tahir; Mazhar Ulhaq; Muhammad Adeeb Khan; Muhammad Tariq Zahid (Environmental Science and Pollution Research, 2020)

Therapeutic role of garlic and vitamins C and E against toxicity induced by lead on various organs - Shumaila Mumtaz; Shaukat Ali; Rida Khan; Hafiz Abdullah Shakir; Hafiz Muhammad Tahir; Samiara Mumtaz; Saiqa Andleeb (Environmental Science and Pollution Research, 2020)

Spatio-Temporal Variability of Summer Monsoon Onset over Pakistan - Shaukat Ali; Bushra Khalid; Rida Sehar Kiani; Romaisa Babar; Sana Nasir; Nadia Rehman; Muhammad Adnan; Muhammad Arif Goheer (Asia-Pacific Journal of Atmospheric Sciences, 2020)

Toxicological effects of toxic metals (cadmium and mercury) on blood and the thyroid gland and pharmacological intervention by vitamin C in rabbits - Rida Khan; Shaukat Ali; Shumaila Mumtaz; Saiqa Andleeb; Mazhar Ulhaq; Hafiz Muhammad Tahir; Muhammad Khalil Ahmad Khan; Muhammad Adeeb Khan; Hafiz Abdullah Shakir (Environmental Science and Pollution Research, 2019)

The protective role of ascorbic acid in the hepatotoxicity of cadmium and mercury in rabbits - Shumaila Mumtaz; Shaukat Ali; Rida Khan; Saiqa Andleeb; Mazhar Ulhaq; Muhammad Adeeb Khan; Hafiz Abdullah Shakir (Environmental Science and Pollution Research, 2019)

Heavy metals transported through a multi-trophic food chain influence the energy metabolism and immune responses of Cryptolaemus montrouzieri - Cailian Du; Jianhui Wu; Muhammad Hamid Bashir; Mobeen Shaukat; Shaukat Ali (Ecotoxicology, 2019)

Renal toxicity of heavy metals (cadmium and mercury) and their amelioration with ascorbic acid in rabbits - Shaukat Ali; Sidra Hussain; Rida Khan; Shumaila Mumtaz; Nasra Ashraf; Saiqa Andleeb; Hafiz Abdullah Shakir; Hafiz Muhammad Tahir; Muhammad Khalil Ahmad Khan; Mazhar Ulhaq (Environmental Science and Pollution Research, 2019)

Seismic vulnerability of non-ductile RC buildings in Pakistan through stochastic analysis of design/construction deficiencies - Muhammad Usman Ali; Shaukat Ali Khan; Muhammad Yousaf Anwar; Uzair Maqbool (Bulletin of Earthquake Engineering, 2019)

Sugarcane bagasse-derived biochar reduces the cadmium and chromium bioavailability to mash bean and enhances the microbial activity in contaminated soil - Saqib Bashir; Qaiser Hussain; Muhammad Akmal; Muhammad Riaz; Hongqing Hu; Shahzada Sohail Ijaz; Muhammad Iqbal; Shaukat Abro; Sajid Mehmood; Munir Ahmad (Journal of Soils and Sediments, 2018)

A measles outbreak in Sindh, Pakistan caused by a genotype B3 virus - Syed Sohail Zahoor Zaidi; Abdul Hameed; Naeem Ali; Massab Umair; Muhammad Masroor Alam; Muhammad Suleman Rana; Salmaan Sharif; Uzma Bashir Aamir; Shahzad Shaukat; Mehar Angez; Adnan Khurshid; Ribqa Akhtar; et al. (Archives of Virology, 2017)

Using Landsat images to monitor changes in the snow-covered area of selected glaciers in northern Pakistan - Chaman Gul; Shi-chang Kang; Badar Ghauri; Mateeul Haq; Sher Muhammad; Shaukat Ali (Journal of Mountain Science, 2017)

Chilling tolerance in three tomato transgenic lines overexpressing CBF3 gene controlled by a stress inducible promoter - Sabir Hussain Shah; Shaukat Ali; Abdul Ahad Qureshi; Muhammad Amir Zia; Jalal-ud -Din; Ghulam Muhammad Ali (Environmental Science and Pollution Research, 2017)

Modeling of Cr contamination in the agricultural lands of three villages near the leather industry in Kasur, Pakistan, using statistical and GIS techniques - Muhammad Shafiq; Tahira Shaukat; Aisha Nazir; Firdaus-e- Bareen (Environmental Monitoring and Assessment, 2017)

Current advancements of magnetic nanoparticles in adsorption and degradation of organic pollutants - Mazhar Ul-Islam; Muhammad Wajid Ullah; Shaukat Khan; Shehrish Manan; Waleed Ahmad Khattak; Wasi Ahmad; Nasrullah Shah; Joong Kon Park (Environmental Science and Pollution Research, 2017)

Health assessment using aqua-quality indicators of alpine streams (Khunjerab National Park), Gilgit, Pakistan - Salar Ali; Junfeng Gao; Farida Begum; Atta Rasool; Muhammad Ismail; Yongjiu Cai; Shaukat Ali; Shujaat Ali (Environmental Science and Pollution Research, 2017)

Piercing and incubation method of in planta transformation producing stable transgenic plants by overexpressing DREB1A gene in tomato (Solanum lycopersicum Mill.) - Sabir Hussain Shah; Shaukat Ali; Sohail Ahmad Jan; Jalal-Ud-Din; Ghulam Muhammad Ali (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Prospects of raising Sahiwal cow calves for veal production under tropical environment - Shaukat Ali Bhatti; Kamran Nazir; Muhammad Jamil Basra; Muhammad Sajjad Khan; Muhammad Sarwar; Muhammad Ashraf Iqbal Mughal (Tropical Animal Health and Production, 2013)

Degradation and Mineralization of Azo Dye Reactive Blue 222 by Sequential Photo-Fenton’s Oxidation Followed by Aerobic Biological Treatment Using White Rot Fungi - Shumaila Kiran; Shaukat Ali; Muhammad Asgher (Bulletin of Environmental Contamination and Toxicology, 2013)

Effect of diet on preweaning performance of Sahiwal calves - Shaukat Ali Bhatti; Muhammad Faisal Ahmed; Peter Charles Wynn; David McGill; Muhammad Sarwar; Muhammd Afzal; Ehsan Ullah; Musarrat Abbas Khan; Muhammad Sajjad Khan; Russell Bush; Hassan Mahmood Warriach; Ahrar Khan (Tropical Animal Health and Production, 2012)

Using leaf tip necrosis as a phenotypic marker to predict the presence of durable rust resistance gene pair Lr34/Yr18 in wheat - Syed Jawad Ahmad Shah; Shaukat Hussain; Musharaf Ahmad; Farhatullah; Iftikhar Ali; Muhammad Ibrahim (Journal of General Plant Pathology, 2011)

Toxic Effect of Cadmium on Rice as Affected by Nitrogen Fertilizer Form - Muhammad Jaffar Hassan; Feng Wang; Shaukat Ali; Guoping Zhang (Plant and Soil, 2005)